Knowledge Of Students' Boarding School to Increase Resistance Immunity During Pandemic Covid- 19 - Apriyani Puji Hastuti; Try Indah Kurniawati; Juliati Koesrini (Jurnal Keperawatan Malang, 2022)
The immune system plays a role in protecting the body when germs first enter the body, therefore it must always be maintained and improved in order to avoid contracting the Covid-19 virus. In the current pandemic conditions reduce activity and reduce mobility. In conditions of adaptation to new habits, good behavior is needed from the community, especially those in a community or group to increase efforts to increase immunity to reduce susceptibility to infection with the covid-19 virus. The aim of this study was to determine the knowledge of female students in increasing endurance. body during the Covid-19 pandemic at the Nurul Ulum Islamic Boarding School, Malang City. The research design in this study was descriptive with a cross-sectional study approach. The population in this study was all students of the Nurul Ulum Islamic Boarding School Malang with 90 people. The sample in this study was some students of the Nurul Ulum Islamic Boarding School in Malang, which were measured using the Slovin formula, namely 73 people. The sampling technique used is a random sampling system. Data collection in this study used a knowledge questionnaire. Data analysis used univariate data analysis using SPSS 23 software. The results showed that the level of knowledge of female students in increasing endurance, most of them had sufficient knowledge as many as 45 respondents (61.7%), a small part had good knowledge as many as 15 respondents (20.5%) and a small part had less knowledge as many as 13 respondents (17.8 %). A good understanding of increasing body resistance during this pandemic is one of the efforts to prevent and break the chain of transmission of covid, in addition to health protocols, regulating lifestyle and eating patterns according to balanced nutrition.